Extra-anatomic left subclavian artery bypass patency in frozen elephant trunk surgeryCentral MessagePerspective - Leon Mattern; Philipp Pfeiffer, MD; Karen Wittemann; Edoardo Zancanaro, MD; Chris Probst, MD; Ahmed Ghazy, MD; Hendrik Treede, MD, PhD; Daniel-Sebastian Dohle, MD, PhD (JTCVS Techniques)
Objective: To explore the advantages and consequences of using an extra-anatomic Dacron bypass in frozen elephant trunk surgery for fast and secure left subclavian artery (LSA) reimplantation. Methods: Between June 2017 and June 2023, 195 patients were treated using an LSA bypass. All postoperative imaging was reviewed to assess the patency of the bypass grafts. If the LSA bypass was not patent, symptoms of complications and their management were evaluated. Time-to-event analysis was performed to assess bypass patency and time to thrombosis. Results: Out of 195 LSA bypasses, 183 remained patent during follow-up, for a 5-year patency rate of 91.4%. Prolonged cardiopulmonary bypass duration was associated with poorer graft patency. Eight of the 12 patients with a thrombosed LSA bypass were asymptomatic. The most common complication of thrombosed bypass was subclavian steal syndrome. Surgical revision was necessary in 2 of the 4 symptomatic patients. All cases of thrombosed LSA bypass occurred within the first 15 months. Conclusions: LSA bypass in frozen elephant trunk surgery is a fast and safe technique for supra-aortic artery reimplantation. Bypass thrombosis is rare and often does not require surgical intervention.